Factors affecting mortality prototype in Murrah buffaloes: A review - Gupta, Nitin Mohan; Mehra, Madan Lal; Malhotra, Puneet (Buffalo Bulletin, 2019)
The theme of investigation was the group of 1230 Murrah buffaloes at the dairy farm of GADVASU, Ludhiana. The research was conducted for the period of forty years 1971 to 2010, to make out the mortality prototype at this organized herd. An overall 1230 animals died because of various causes during these forty years, which accounted for overall mortality of 29.36% of total herd. Maximum mortality in different age groups of calves was due to affections of digestive system. Mortality up to one month of age was 52.35% indicating that almost half of the calves died during first month of age. The mortality rate declined to 11.95% up to three month of age in calves and mortality rate further declined to 5.44% up to six month of age. The mortality rate further declined to 4.88% of total mortality up to one year of age. The cumulative mortality up to one year of age was 74.62%, which indicated that two-third of the total mortality occurred up to one year of age. Out of all the lactations maximum mortality is found in first lactation and minimum mortality is observed in 10th and above lactation. Higher incidence of mortality was found to be in the month of August 13.5% while lowest mortality percentage is found in the month of October i.e. 3.52.